Komentarz do Bibliografii przekładów literatury słowackiej w Polsce w 2015 roku - Buczek, Marta (Przekłady Literatur Słowiańskich, 2016)
A commentary on the Bibliography of Slovak literary translations in Poland in 2015 The author of the article considers the latest translations of Slovak literature in Poland in 2015. Among very well -known and valued Slovak authors whose translations have been published recently are contemporary and modern authors of the younger generation (Pavol Rankov, Peter Krištúfek, Maroš Krajňak, Jana Beňova) and the older generation (Pavel Vilikovský, Daniela Kapitaňová). Their books were very well received by Polish recipients and it occurs that Slovak literature in Poland is read with steadily growing interest. The article concerns Polish translations of Slovak poetry as well. The survey shows a decreasing number of translations of this kind of literature. In 2015 only three small anthologies of poetry were published. In this way, Slovak poetry was represented by a few local poets (Radovan Brenkus and Pavol Hudák). Key words: Slovak literature, Slovak literature in Poland, translation, literary translation, Pavol Rankov, Peter Krištúfek, Maroš Krajňak, Jana Beňova, Radovan Brenkus, Pavol Hudák